Development and characterization of new Ti-25Ta-Zr alloys for biomedical applications - Kuroda, Pedro Akira Bazaglia [UNESP] (2021)
This paper deals with the study of the development, structural and microstructural characterization and, selected mechanical properties of Ti-25Ta-50Zr alloy for biomedical applications. The alloy was melted in an arc furnace and various solution heat treatments were performed to analyze the influence of the temperature and time on the structure, microstructure, microhardness and elastic modulus of the samples. The structural and microstructural results, obtained by X-ray diffraction and microscopy techniques, showed that the solution heat treatment performed at high temperatures induces the formation of the β phase, while solution heat treatment performed at low temperatures induces the formation of the α and ω metastable phases. Regarding the effect of time, samples subjected to heat treatment for 6 hours have only the β phase, indicating that lengthy treatments suppress the α phase. Regarding the hardness and elastic modulus, the alloy with the α and ω phases, after treatment performed at a temperature of 500 °C, has a high hardness value and elastic modulus due to the presence of the ω phase that hardens and weakens alloys. The titanium alloys developed in this study have excellent mechanical properties results for use in the orthopedic area, better than many commercial materials such as cp-Ti, stainless steel and Co-Cr alloys.